2009
DOI: 10.1016/j.rmed.2008.12.017
|View full text |Cite
|
Sign up to set email alerts
|

Office spirometry can improve the diagnosis of obstructive airway disease in primary care setting

Abstract: Telespirometry, performed in a GP's office, can aid the diagnosis of obstructive airway diseases and could help GPs to better manage airway obstruction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 34 publications
0
31
0
1
Order By: Relevance
“…The Alliance Project has investigated telespirometry in Italian general practices with rapid reporting by a pulmonary specialist. 26 This project found severe obstruction in some symptomatic undiagnosed patients and also misdiagnosis of COPD in patients with normal spirometry.…”
Section: Qualitative Datamentioning
confidence: 91%
“…The Alliance Project has investigated telespirometry in Italian general practices with rapid reporting by a pulmonary specialist. 26 This project found severe obstruction in some symptomatic undiagnosed patients and also misdiagnosis of COPD in patients with normal spirometry.…”
Section: Qualitative Datamentioning
confidence: 91%
“…Overall, the authors concluded that telespirometry was well accepted by these Italian GPs. A somewhat similar study was conducted by the same authors (published in 2009), 117 wherein 638 GPs were trained to perform telespirometry on four sets of subjects: (1) smokers and ex-smokers without respiratory symptoms, (2) patients with respiratory symptoms but not diagnosed, (3) patients diagnosed with asthma, and (4) patients diagnosed with COPD. All traces were interpreted by specialists.…”
Section: Feasibility and Acceptancementioning
confidence: 97%
“…Les difficultĂ©s Ă  obtenir des manoeuvres de bonne qualitĂ© ne sont pas toujours Ă©voquĂ©es dans les enquĂȘtes Ă©pidĂ©miologiques basĂ©es sur la spiromĂ©trie. Notre expĂ©rience n'est toutefois pas trĂšs diffĂ©rente de ce qui est rapportĂ© dans d'autres enquĂȘtes basĂ©es sur une spiromĂ©trie rĂ©alisĂ©e par les mĂ©decins traitants, oĂč seulement 60 Ă  78 % des examens sont considĂ©rĂ©s « acceptables » [27,28]. Ces difficultĂ©s techniques sont Ă  considĂ©rer avant de promouvoir la spiromĂ©trie en tant qu'examen de dĂ©pistage de la BPCO par des mĂ©decins non spĂ©cialistes.…”
Section: Discussionunclassified